2018
DOI: 10.1002/lio2.186
|View full text |Cite
|
Sign up to set email alerts
|

Oral L‐thyroxine liquid versus tablet in patients submitted to total thyroidectomy for thyroid cancer (without malabsorption): A prospective study

Abstract: ObjectiveNo consistent data are present in literature about the effectiveness of Levothyroxine (L‐T4) liquid formulation in patients without malabsorption after thyroidectomy. The aim of this study is to compare the effectiveness of L‐T4 liquid formulation, with L‐T4 tablets, in thyroid cancer patients after thyroidectomy (without malabsorption or drug interference).MethodsOne hundred five patients were recruited; 52 patients were treated with liquid L‐T4 formulation, while 53 with L‐T4 tablets, at the same do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 33 publications
(62 reference statements)
2
19
1
2
Order By: Relevance
“…There is abundant evidence showing that under the said dietary, pharmacologic or digestive system-associated conditions of undertreated primary hypothyroidism, switch from the tablet to either liquid or softgel capsule (so-called novel formulations) normalizes serum TSH levels [2], [3], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19]. Evidence for lower TSH levels, in both replacement and TSH-suppressive settings, under the novel formulations compared to the tablet formulation has also been obtained in the absence of those conditions [20], [21], [22], [23], [24], [25], [26], [27], [28] and, for sake of completeness of information, in central hypothyroidism [29]. All this evidence stems from the more favorable pharmacokinetics profile of the two novel formulations compared to the tablet formulation [3], [30], [31], [32].…”
Section: Introductionmentioning
confidence: 80%
“…There is abundant evidence showing that under the said dietary, pharmacologic or digestive system-associated conditions of undertreated primary hypothyroidism, switch from the tablet to either liquid or softgel capsule (so-called novel formulations) normalizes serum TSH levels [2], [3], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19]. Evidence for lower TSH levels, in both replacement and TSH-suppressive settings, under the novel formulations compared to the tablet formulation has also been obtained in the absence of those conditions [20], [21], [22], [23], [24], [25], [26], [27], [28] and, for sake of completeness of information, in central hypothyroidism [29]. All this evidence stems from the more favorable pharmacokinetics profile of the two novel formulations compared to the tablet formulation [3], [30], [31], [32].…”
Section: Introductionmentioning
confidence: 80%
“…Three studies with 266 participants concerned comparison of liquid and tablet LT4 effectiveness of suppressive therapy in patients with DTC [30][31][32]. Two of them including 207 patients were prospective, randomised, and concluded that the use of LT4 liquid formulation, as compared to tablets, provided better control of TSH and resulted in a significantly higher number of DTC patients maintaining TSH values within range for the ATA risk score and reducing TSH variability over time [31,32]. Conversely, Giusti et al in a small study with 59 participants did not find any differences in TSH and thyroid hormone concentrations between the tablet and liquid L-T4 groups [30].…”
Section: Comparison Of the Effectiveness Of Liquid And Tablet Levothymentioning
confidence: 99%
“…Trzy badania poświęcono porównaniu skuteczności działania LT4 stosowanej w płynie lub w tabletkach w leczeniu supresyjnym 266 chorych na ZRT [30][31][32]. Dwa z nich, w których uczestniczyło 207 chorych, były randomizowanymi badaniami prospektywnymi.…”
Section: Porównanie Skuteczności Działania Lewotyroksyny W Postaci Płunclassified
See 1 more Smart Citation
“…Mistry et al achieved a predicted levothyroxine dose of 1.6 mcg/kg after total thyroidectomy (5). Also, Fallahi et al reported the mean postoperative levothyroxine dose of 1.5 for total thyroidectomy (21).…”
Section: Discussionmentioning
confidence: 99%